2022
DOI: 10.1002/ppap.202100215
|View full text |Cite
|
Sign up to set email alerts
|

Time resolved study of ignition of microwave discharge in liquid hydrocarbons

Abstract: Results of the study of acoustic phenomena and changes in the structure of the microwave (2.45 GHz) discharge in liquid hydrocarbons in time are presented. Discharge was ignited at the tip of microwave antennas with conical or rounded ends. Petroleum solvent Nefras was chosen as representative of liquid hydrocarbons. Electret microphone and high-speed video cameras were used to study the discharge. It is shown that the discharge is always attached to the top of the cone in the case of the conical end of the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Before discussing the results obtained, let us describe in general terms some physical processes that occur in a microwave discharge in liquids, since it is these processes that largely determine the features of the results obtained in comparison with those obtained in conventional gas discharges. The physical picture of the processes in such discharges was studied in by Lebedev et al [27,28] The discharge occurs at the microwave antenna in the region where the liquid evaporates and the microwave field strength is sufficient for breakdown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before discussing the results obtained, let us describe in general terms some physical processes that occur in a microwave discharge in liquids, since it is these processes that largely determine the features of the results obtained in comparison with those obtained in conventional gas discharges. The physical picture of the processes in such discharges was studied in by Lebedev et al [27,28] The discharge occurs at the microwave antenna in the region where the liquid evaporates and the microwave field strength is sufficient for breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental setup used for generation of microwave discharge in liquid hydrocarbons was described in detail in by Lebedev et al [ 27,28 ] and schematically is shown in Figure 1. The microwave system includes the elements needed to generate, control and measure the incident microwave power.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the experimental setup was provided in [41,42], and the setup is schematically shown in Figure 1. It consists of a magnetron generator (2.45 GHz) and a system for controlling and measuring the microwave power entering the reactor (200-350 W).…”
Section: Methodsmentioning
confidence: 99%
“…The antenna was immersed in the liquid during the experiments at atmospheric pressure above the liquid surface. Different optical methods in the visible wavelength range were used to study the discharge: a BS520 photodiode for visible light was used to study the total intensity of discharge radiation (the signal was measured using an AKIP-4126/3A-X 4-channel oscilloscope), and an AvaSpec-3628 gated spectrograph (wavelength range of 172-744 nm, spectral resolution of 1 nm, and shutter speed of 1 ms) was used to study the time-resolved discharge emission [41,42]. The "Specair-3.0" program was used to analyze the measured spectra [43].…”
Section: Methodsmentioning
confidence: 99%